EDUCATION AND SOCIO-CULTURAL REPRODUCTION: DEVELOPMENT OF TRIBAL PEOPLE IN WAYANAD, KERALA - SUSAMMA ISAC (RAJAGIRI JOURNAL OF SOCIAL DEVELOPMENT, 2012)
This paper discusses how schooling reproduces social inequalities and cultural asymmetries in contemporary India by examining the experiences of two tribal communities (the Paniyas and the Kurichiyas) in the Wayanad district of Kerala. There are notable socio-economic and cultural inequalities between these two tribal communities. The Paniyas are more backward and disadvantaged than the Kurichiyas. This social differentiation is reproduced through the present schooling system. The Paniyas experience discrimination in school and lag behind the Kurichiyas in educational achievement. An important pedagogic problem faced by the Paniyas in school is their inability to cope with the schooling provided through a language that is not their mother tongue. Land ownership, and the cultural and social capital resulting from it place the Kurichiya community at a comparatively better position than the Paniyas, who have a labour class and slave caste identity. Access to land is critical for the socioeconomic and educational development of tribal communities.